Empowering Women through Education: Trends of Literacy Rate and Its Impact on Fertility and Mortality in Nepal - Adhikari, Shanta Upadhya; Adhikari , Surya Prasad (Curriculum Development Journal, 2025)
This study examines the relationship between female literacy and key demographic indicators, fertility and mortality over the period 1971 to 2021. The main objective of this study is to explore trends in female literacy and examine their association with national fertility and mortality patterns in Nepal. Employing a descriptive and analytical research design, this study utilizes secondary data from national population censuses, the National Demographic Health Survey (NDHS), peer reviewed journals, academic texts, and authoritative online sources. The findings demonstrate a marked increase in female literacy rates alongside significant declines in fertility and mortality rates. The evidence of this study supports that improved education of females contributes to improved reproductive health outcomes, including delayed marriage, increased use of family planning, childbearing, and reductions in maternal mortality and child mortality. Furthermore, the study situates Nepal’s progress within the regional and global context, highlighting the importance of continued investment in female education to address demographic challenges like the reduction of fertility and mortality rates. This study explores the important role of female education as a catalyst for population management and health improvements in maternal and child health in Nepal.